2013
DOI: 10.4161/hv.23795
|View full text |Cite
|
Sign up to set email alerts
|

Improving adherence rates to a cocooning program

Abstract: Cocoon is defined as a strategy to reduce the risk for transmission of pertussis to newborn infants by vaccinating household members including parents and siblings. Programmatic challenges make implementation of cocooning program complex. At the local health care unit “ASL Napoli 1 Centro,” a one-year pilot project to evaluate the newborn contacts adherence to a cocoon strategy was started on May, 1st 2011. Healthcare providers (HCPs) offered for free a dTpa booster dose to newborns parents (mothers were immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
(27 reference statements)
0
5
0
3
Order By: Relevance
“…31 Moderate uptake rates were also reported in select programs in Europe. 32,33 However, a study in Canada noted poor cost -effectiveness for cocooning when pertussis incidence was low, 34 and outcome studies performed in the US and Australia demonstrated little or modest clinical effectiveness of cocooning. [35][36][37] These studies demonstrate the inherent limitations of cocooning as a stand-alone pertussis prevention strategy for infants, although it remains a recommended component of a multi-faceted approach to decrease pertussis disease burden.…”
Section: Control Strategiesmentioning
confidence: 99%
“…31 Moderate uptake rates were also reported in select programs in Europe. 32,33 However, a study in Canada noted poor cost -effectiveness for cocooning when pertussis incidence was low, 34 and outcome studies performed in the US and Australia demonstrated little or modest clinical effectiveness of cocooning. [35][36][37] These studies demonstrate the inherent limitations of cocooning as a stand-alone pertussis prevention strategy for infants, although it remains a recommended component of a multi-faceted approach to decrease pertussis disease burden.…”
Section: Control Strategiesmentioning
confidence: 99%
“…Kozaya alınan yenidoğan, bakım vericileri de dâhil olmak üzere, sosyal çevresi enfeksiyon etkenine karşı aşılandığından, dolaylı olarak koruma altına alınmış olmaktadır. 40 Koza stratejisinin, özellikle boğmaca ve influenza enfeksiyonlarının epidemi dönemlerinde etkili olduğu belirtilmektedir. 29,39 Günümüzde Almanya, Fransa, İtalya, İspanya, İsviçre, Yunanistan, Hollanda, ABD, Avustralya, Kanada, Brezilya ve Şili gibi dünyanın pek çok ülkesinde yenidoğanları boğmacaya karşı korumak için bu yöntem uygulanmaktadır.…”
Section: Koza Strateji̇si̇ (Cocooning Strategy)unclassified
“…24, 29 Simonetti ve ark.nın yaptıkları çalışmada, sağlık profesyonelleri ile aileler arasında kurulan iletişimin güçlendi-rilmesi ile koza programına katılım oranının %2,6'dan %78,8'e yükseldiği belirlenmiştir. 40 Decrequy ve ark.nın çalışmasında, koza programıyla boğmaca etkenine karşı aşılanmak isteyen ailelerin oranının bir yılın sonunda yaklaşık beş kat arttığı saptanmıştır. 26 Hollanda'da yapılan bir çalışmada, ailelerin boğmaca koza programına katılma isteklerinin %78 olduğu bulunmuştur.…”
Section: Koza Strateji̇si̇ (Cocooning Strategy)unclassified
See 1 more Smart Citation
“…This was highlighted by a recent educational program implemented in an Italian hospital. 54 Initially, a free postpartum DTaP booster dose was offered to parents and household contacts, but only 3% of the invited families participated. To increase uptake, an educational program was introduced, HCPs were recruited and engaged, and interactions with the families were increased during visiting hours.…”
Section: Challenges To Implementing Cocooningmentioning
confidence: 99%